How to analyse the enabling environment for designing your intervention - Minh, Thai Thi; Ofosu, Abena (International Water Management Institute, 2023)
Through analyzing policies and interventions and exploring the context, enabling environment analysis assesses the current situation that influences the design and impact of the scaling investments and supports.